Pulping of Illuk Grass (Imperata arundinacea) by Soda and Mono-sulphite Processes - Singh, Chattar; Guha, S. R. D. (Indian Forester, 1951)
At the request of the Ceylon Government, investigations were carried out at the Forest. Research Institute, Dehra Dun, on the pulping of illuk grass (Imperata arundinacea) by monosulphite and soda processes with a view to ascertaining the respective economies of the two processes. The sample of grass was supplied by the Ceylon Government. The investigations have disclosed that the cost of chemicals required for pulping of the grass by the mono-sulphite process is 38% more than that required by the soda process. Of the two methods of digestion, namely "overhead" and "fractional" as applicable to the soda process, "fractional" method of digestion appears to be more suitable as well as more economical for pulping of illuk grass.